Safe Injections Sites: Insurgent Architecture? Drug Use and Learning as Social Practice - Jean Flynn (Adult Education Research Conference, 2004)
Within the context of a safe injection site, this paper will explore a social theory of learning that supports the importance of the everyday learning processes of people within communities of practice.